Scaling Rules of SERS Intensity. Issue 4 (12th February 2014) - Nishijima, Yoshiaki; Hashimoto, Yoshikazu; Rosa, Lorenzo; Khurgin, Jacob B.; Juodkazis, Saulius
<x xml:space="preserve">Abstract</x> An intricate relationship is revealed between the intensity of surface‐enhanced Raman scattering (SERS) and the optical extinction. The unusual trends of SERS intensity decrease while the extinction increases observed in experiments is fully explained for the first time. The SERS intensity is well known to be strongly correlated with the extinction at excitation and Stokes wavelengths, but the dependence is more involved than the simple product of the two extinction enhancements. The radiative and nonradiative losses, different for different Stokes wavelengths, strongly affect the relationship between SERS and extinction. Dye molecules are shown experimentally and numerically to experience different local field enhancements for the different Raman modes, and a simple qualitative analytical description of this universal phenomenon is provided here.